Managerial techniques required of principals of technical and vocational colleges for quality assurance and skill acquisition - Odo, Moses Ikebe (Jurnal Pendidikan Teknologi Kejuruan, 2023)
The study is on the Managerial Techniques Required of Principals of Technical and Vocational Colleges for Quality Assurance and Skill Acquisition. The study was carried out in Lagos State. It covered all the six (6) technical colleges in the state. Survey design was used to elicit information from the respondents. The population of the study included all the Principals, and Vice Principals, departmental and unit heads. A total of six principals, twelve vice principals, five departmental heads and fifteen unit heads were used for the study. A pilot study was conducted to ascertain the reliability of the questionnaire items which was calculated to be 0.69. Five research questions were raised for the study and the data collected analysed with mean and standard deviation. The result of the study showed that Principals of technical and vocational colleges apply some levels of managerial skills though do not involve teachers in policy and decision making, Most of the managerial techniques of Principals of technical and vocational colleges are not very adequate to enhance the quality of technical and vocational education.